The Relationship of Physical Fitness to Learning Outcomes in Grade 5 Students of SD Sejahtera 4 Bandar Lampung - Sebastianus Rino Setia Putra; Joan Siswoyo; Alifia Ramadhina Putri; Candra Kurniawan (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aimed to determine the relationship between physical fitness and learning outcomes among fifth-grade students at Sejahtera 4 Elementary School, Bandar Lampung. This research employed a quantitative approach using a correlational method. The population of this study consisted of all fifth-grade students totaling 30 students. Data collection techniques included the Indonesian Physical Fitness Test (Tes Kebugaran Jasmani Indonesia/TKJI) Phase C to measure students’ physical fitness, while learning outcomes data were obtained from the Mid-Semester Assessment scores in Physical Education (PJOK). Data analysis was conducted using the Product Moment correlation test with a significance level of 5%. The results showed a significant relationship between physical fitness and students’ PJOK learning outcomes at the elementary school level, with a correlation coefficient of r = 0.413 and a significance value of p = 0.023 (p < 0.05). This indicates that the better the students’ level of physical fitness, the higher their PJOK learning outcomes. Therefore, it can be concluded that physical fitness plays an important role in supporting the achievement of PJOK learning outcomes among elementary school students.